2003
DOI: 10.1164/rccm.200209-1116oc
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Montelukast on Surrogate Inflammatory Markers in Corticosteroid-treated Patients with Asthma

Abstract: We evaluated whether montelukast conferred additive effects in patients with asthma receiving fluticasone/salmeterol (FP/SM) combination and FP alone. Twenty-two patients with mild to moderate asthma completed a double-blind, placebo-controlled study. After a 2-week run-in using FP 250 microg/SM 50 microg 1 puff twice daily, patients entered a randomized crossover period to receive additional montelukast 10 mg daily or placebo for 3 weeks each. For the first 2 weeks, they received FP/SM 1 puff BID, and then th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
43
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 100 publications
(51 citation statements)
references
References 33 publications
8
43
0
Order By: Relevance
“…The 6.9¡12.4% pred FEV1 response noted after montelukast compared with placebo is comparable to findings from other studies, which showed improvements of ,7% pred from baseline [28][29][30]. The 6.5% pred improvement in FEF25-75% did not reach statistical significance, but agrees well with an 8% pred response seen in a prior study [28].…”
Section: Discussionsupporting
confidence: 87%
“…The 6.9¡12.4% pred FEV1 response noted after montelukast compared with placebo is comparable to findings from other studies, which showed improvements of ,7% pred from baseline [28][29][30]. The 6.5% pred improvement in FEF25-75% did not reach statistical significance, but agrees well with an 8% pred response seen in a prior study [28].…”
Section: Discussionsupporting
confidence: 87%
“…This, therefore, explains why there are additive effects of LTRAs to inhaled corticosteroids. In another study [26] in corticosteroid treated asthmatics, there was an additive effect on BHR to AMP plus blood eosinophils and exhaled NO. In other words, there is a nonsteroidal mediated component to BHR which can be attenuated 20 for LTRA minus placebo divided by log 10 2 (i.e.…”
Section: Discussionmentioning
confidence: 89%
“…The current authors do not believe that this is a weakness of the study, since montelukast binds reversibly to the leukotriene receptor, reaches steady state by day 2 and has a plasma terminal halflife of 5.3 h (up to 6.6 h in the elderly); this suggests that its clinical effects last, at most, for 33 h (five half-lives) [24]. Furthermore, several previous crossover trials examining the efficacy of adding montelukast to placebo in subjects on corticosteroids have omitted a washout period without evidence of carry-over interactions [25][26][27]. For example, a two-period, 16-week crossover trial, with a 2-week run-in phase, comparing the effect of adding montelukast or placebo to subjects with mild asthma already on fluticasone proprionate, found similar insignificant reductions in inflammatory cells on bronchial biopsy [27].…”
Section: Discussionmentioning
confidence: 99%